PENERAPAN TEKNOLOGI TEPAT GUNA PENGRAJIN TEMPE DUSUN LATSARI UNTUK MENINGKATKAN PRODUKTIVITAS - Wulandari, Lusi Mei Cahya; Patrick, Johan; Yoseph, Deograsias; Sumewang, Filippo (Abdi Panca Marga, 2023)
In facing tough competition, tempe small and medium enterprises (SMEs) need to pay attention to the arrangement of their production facilities. A well-organized and tidy production facility helps improve production process efficiency. This has an impact on the quality of tempe, ensuring it meets the established standards. Desa Mlirip in Jetis sub-district, Mojokerto, has seven Tempe Home Industries (IRT) with the largest production located in Dusun Latsari, owned by Mr. Riono, with a minimum daily production of 600 kg. The issue faced by the partners is that the soybean washing process is done manually, which leads to employee fatigue and a lack of hygiene. The goal of this Community Partnership Program is to increase the productivity of tempe producers through the creation of a soybean washing machine, resulting in a faster production process and better product quality. The steps taken include designing a 100kg capacity washing machine, manufacturing the machine, conducting trials, and implementing the machine on the production floor. The results of implementing the soybean washing machine have led to a 27.70% cost savings and have lightened the workload for operators at the tempe business in Dusun Latsari. Keywords: Tempeh, Soybean Washing Machine; Productivity